6n-9(5-n)=-12(n+6)

Simple and best practice solution for 6n-9(5-n)=-12(n+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n-9(5-n)=-12(n+6) equation:


Simplifying
6n + -9(5 + -1n) = -12(n + 6)
6n + (5 * -9 + -1n * -9) = -12(n + 6)
6n + (-45 + 9n) = -12(n + 6)

Reorder the terms:
-45 + 6n + 9n = -12(n + 6)

Combine like terms: 6n + 9n = 15n
-45 + 15n = -12(n + 6)

Reorder the terms:
-45 + 15n = -12(6 + n)
-45 + 15n = (6 * -12 + n * -12)
-45 + 15n = (-72 + -12n)

Solving
-45 + 15n = -72 + -12n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '12n' to each side of the equation.
-45 + 15n + 12n = -72 + -12n + 12n

Combine like terms: 15n + 12n = 27n
-45 + 27n = -72 + -12n + 12n

Combine like terms: -12n + 12n = 0
-45 + 27n = -72 + 0
-45 + 27n = -72

Add '45' to each side of the equation.
-45 + 45 + 27n = -72 + 45

Combine like terms: -45 + 45 = 0
0 + 27n = -72 + 45
27n = -72 + 45

Combine like terms: -72 + 45 = -27
27n = -27

Divide each side by '27'.
n = -1

Simplifying
n = -1

See similar equations:

| -8=-2(x+3)-4 | | 555x+15=666 | | 2x-5=-3a | | -5-3n+-2n+7n= | | -(2x+2)-4x-2=3x+2 | | x^2+8x+-5=15 | | x-3/5=-2/3 | | 9x+21=15 | | A+21=-4(-8a+3)+2a | | 11x+3x-5=-(-x+5) | | 2+n=-9/2 | | 3x+4x-1+1=5x-6x+3 | | -2/3b+2/5=64-5 | | 1+7b=3(1+2b)+3b | | 3a+7=-22 | | 6-x+2=3x+2+2x | | -5x-x+3=-33 | | 3n/5+9/10+n/5=23/10 | | 3n-15=-22 | | m-3/5=0 | | 31=2-3x-1+5x | | 2/3(3x-9)15 | | 2(6x-7)=-2+6(11x-2) | | 8(2y-3)-5y=20 | | y/20=4 | | M=x+b/p | | -3(4-2x)+3=3 | | 5/2x+2x=3/2 | | X-9/5+3/4=-61/20 | | z^2+2*sqrt(-1)*z-1-2*sqrt(-1)=0 | | -40-7x=6(1-5x) | | z^2-2iz-1-2i=0 |

Equations solver categories